Molecular uropathology: what a practising pathologist should know - Bahlinger, Veronika; Lange, Fabienne; Eckstein, Markus (Diagnostic Histopathology, 2024)
Advancements in molecular pathology have initiated a transformative era in the diagnostic classification and treatment of urological cancers. The 2022 WHO classification exemplifies this evolution by introducing molecularly defined renal cell carcinoma entities. The synthesis of clinical, pathological, and molecular findings leveraging large-scale technologies like next-generation sequencing (NGS) has led to a significant acceleration of precision oncology. Predictive biomarker testing has gained significant importance in urological malignancies, especially in urothelial cancer and prostate cancer underscored by novel targeted drugs like Erdafitinib and PARP inhibitors. Furthermore, immunotherapy has emerged as a central pillar in managing kidney cancer and urothelial cancer. Given the circumstance that many precision oncology trials are currently on the way, molecular diagnostic and especially predictive uropathology will rapidly evolve in the upcoming years. The present review focuses on new developments in molecular uropathology in both fields, diagnostic and predictive molecular uropathology.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Diagnostic molecular pathology; FGFR3 testing; molecular pathology; molecular subtypes; PD-L1 testing; urothelial cancer